2016
DOI: 10.5761/atcs.oa.15-00225
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Vasoreactivity is Equally Affected by <i>In Vivo</i> Cross-Clamping with Increasing Loads in Young and Middle-Aged Mice Aortas

Abstract: Purpose: To compensate for the lack of haptic feedback by surgical robots, limitation of exerted forces could be implemented. The limits should be based on the observed relationship between tissue load and induced damage. This study examines whether age-related changes influence this relationship. Methods: Descending thoracic aortas of male C57BL/6J mice of 10, 25 and 40 weeks were clamped in vivo (no clamp, 0.5N or 2.0N) for 2 min. Functional integrity was tested in vitro by studying endothelium-dependent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This might be an explanation for the absence of a statistical effect of clamping in the chronic time points. The somewhat lower baseline endothelial function after 1 month might be caused by slow deterioration of endothelial function with aging [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be an explanation for the absence of a statistical effect of clamping in the chronic time points. The somewhat lower baseline endothelial function after 1 month might be caused by slow deterioration of endothelial function with aging [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we aim at studying the effect of age and atherosclerosis on load-induced aortic damage in well-controlled experimental mouse models, well known by our group. We have previously shown that clamping thoracic mouse aortas up to 2.0N (6 times the minimal occlusion force) [ 3 ] induces damage in C57BL/6J mice of 10, 25 and 40 weeks of age, without important differences in vascular wall response between these age groups [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies indicate that arterial occlusion by almost any type of clamp systematically leads to intimal injury at the site of application. For example, endothelial denudation is a widely known effect of clamping (Slayback et al, 1976 ; Barone et al, 1989 ; Margovsky et al, 1997 , 1999 ; Hangler et al, 2008 ; Vural et al, 2008 ; Famaey et al, 2010 ; Geenens et al, 2016a , b ). Several studies also report damage to the extracellular matrix (ECM) in the media with flattened elastic lamellae (Barone et al, 1989 ; Margovsky et al, 1999 ; Famaey et al, 2010 ; Geenens et al, 2016a ).…”
Section: Introductionmentioning
confidence: 99%
“…The tonicity of vascular smooth muscle cells (SMC) after clamping was also studied extensively (Barone et al, 1989 ; Famaey et al, 2010 ; Geenens et al, 2016b ). Experimental data on the effects of arterial clamping were collected in mice (Geenens et al, 2016a , b ). In this study, descending thoracic aortas were clamped at different levels of loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation